Preparation and In Vitro Evaluation of Aspartic/Alginic Acid Based Semi-Interpenetrating Network Hydrogels for Controlled Release of Ibuprofen - Muhammad Suhail; Yi-Han Hsieh; Arshad Khan; Muhammad Usman Minhas; Pao-Chu Wu (Gels, 2021)
Different combinations of polymers, aspartic acid (ASP), alginic acid (AL), and monomer acrylic acid (AA) were crosslinked in the presence of an initiator ammonium peroxodisulfate (APS) and cross-linker ethylene glycol dimethacrylate (EGDMA) to develop aspartic acid/alginic acid-co-poly(acrylic acid) (ASP/ALPAA) (semi-interpenetrating polymer network (SIPN)) hydrogels by the free radical polymerization technique for the controlled delivery of ibuprofen (IBP). Various studies such as dynamic swelling studies, drug loading, in vitro drug release and sol−gel analysis were carried out for the hydrogels. Higher swelling was observed at higher pH 7.4 as compared to lower pH 1.2, due to the presence of carboxylic groups of polymers and the monomer. Hence, pH-dependent swelling was exhibited by the developed hydrogels which led to a pH-dependent drug release and vice versa. The structural properties of the hydrogels were assessed by FTIR, PXRD, TGA, DSC, and SEM which confirmed the fabrication and stability of the developed structure. FTIR analysis revealed the reaction of both polymers with the monomer during the polymerization process and confirmed the overlapping of the monomer on the backbone of the both polymers. The disappearance of high intense crystalline peaks and the encapsulation of the drug by the hydrogel network was confirmed by PXRD. TGA and DSC showed that the developed hydrogels were thermally more stable than their basic ingredients. Similarly, the surface morphology of the hydrogels was analyzed by SEM and showed a smooth surface with few pores. Conclusively, ASP/ALPAA hydrogels have the potential to deliver IBP for a long period of time in a controlled way.